Microstrip Line Fed Leaky Wave Antenna with Shorting Vias for Wideband Systems - T V Rama Krishna; B T P Madhav; G Monica; V Janakiram; S Md Abid Basha (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In this work a complex structured shorted vias microstrip leaky wave antenna is designed and analysed. A Leaky wave antenna is a travelling wave structure with complex propagation constant. When shorting vias are loaded in a periodic structure the fundamental resonant mode shows some stop band characteristics and some of the modes will strongly attenuated. Three different types of iterations are examined in this work with and without defected ground structures. The defected ground structure based leaky wave antennas are showing better performance characteristics with respect to efficiency and phase. A micro strip line feeding with impedance of 50 ohms at both ports are providing excellent impedance matching to the conducting path on the microstrip surface. The shorting vias are suppressing certain higher order frequency bands and providing excellent wide band characteristics with low loss.